Deep focus : reflections on cinema - Ray, Satyajit, 1921-1992.; Ray, Sandip, 1954-; Chatterjee, Dhritiman, 1945- (New Delhi : Published by HarperCollins Publishers India, a joint venture with The India Today Group in association with Society for the Preservation of Satyajit Ray Films, 2011)
Articles written by Satyajit Ray, 1921-1992, motion picture director from West Bengal, India; chiefly on motion pictures.
Articles; most previously published.
Includes filmography (p. 138-161) and index.
Keywords: Ray, Satyajit, -- 1921-1992 -- Criticism and interpretation; Motion picture producers and directors -- India; Motion pictures -- India -- History; Motion pictures -- History